Structural morphology and in vitro toxicity studies of nano- and micro-sized zinc oxide structures. Issue 1 (March 2015) - Ann, Ling Chuo; Mahmud, Shahrom; Seeni, Azman; Bakhori, Siti Khadijah Mohd; Sirelkhatim, Amna; Mohamad, Dasmawati; Hasan, Habsah
Graphical abstract